The Influence of Brand and Price on Suzuki Motorcycle Purchase Decisions at PT. Sinar Galesong Pratama Palu City - Rajindra; Farid; Burhanuddin; Salmiati; Guasmin; Nasrulhak Akkas (Universitas Muhammadiyah Palu, 2022)
Todays business competition is getting more challenging because every organization is relied on to compete and build a robust system. Therefore, competition at present cannot be avoided by companies for example, companies engaged in trading, especially PT. Sinar Galesong Pratama Palu. Even with this competition, it is essential to move the company to marketing exercises. By looking at the changing desires of buyers, businesses are required to understand what buyers expect according to the customers choice, one of the models is seen from the section the quality of the brand and as far as price. The reason for doing this research is to find out, the influence of brand quality and cost on the choice of buying a Suzuki motorcycle at PT. Sinar Galesong Pratama Palu. Logical strategy used in this examination is the analysis technique of multiple linear regression. The number of samples used is 100 respondents. The results showed that all factors, brands and costs affect purchasing decisions. It is hoped that management should improve its marketing program to compete with other competitors.